Stillbirth: Incidence, causes and risk factors. 1992-1993 National Hospital Cayetano Heredia. - Salvador, Jorge (2015)
In order to determine the incidence, causes and risk factors associated to fetal death, trying to establish what the change would be in the study population if a factor is neutralized, a prospective study of the cohort type was held in the National Hospital Cayetano Heredia, based on the analysis of perinatal data computer system of all births in the years 1992 - 1993. 192 stillbirths found a total of 8309 births, fetal death rate of 23.1 per 1000 born. The causes of death are infection (28%), hemorrhage (20%) and toxemia (14%). Risk factors of fetal death are: kill-multiparity (RR 2.3), induced labor (RR = 3.5), CPN (RR = 4), breech presentation (RR = 5.1), maternal diseases (RR = 5.5), preterm delivery (RR = 17). Maternal disease, the most important were: bleeding in the second quarter (RR = 19), preterm delivery (RR = 10.6), HTT (RR = 8.5), other infections (RR = 5.8) , eclampsia (RR = 5.7), IUGR (RR = 4), multiple pregnancy (RR = 3.4), RPM (RR = 2), fetales- maternal LBW (RR = 22), prematurity (RR = 21 ), PEG (RR = 6), fetales.- congenital malformations (RR = 5.2). The risk factors to be modified produce a greater reduction of fetal death are: BPN (RAP = 0.65), CPN (RAP = O, 65), preterm delivery (RAP = O, 64), maternal pathology (RAP = 0.59). prematurity (RAP = 0.58), PEG (RAP = 0.23), breech (RAP = 0.16 HTT (RAP = 0.13), preterm labor (RAP = 0.120) and RPM (RAP:. 0 09).